A Manifesto, in 140 Characters or Fewer: Social Media as a Tool of Rebel Diplomacy. Issue 2 (12th April 2017) - Jones, Benjamin T.; Mattiacci, Eleonora
Abstract : Can rebel organizations in a civil conflict use social media to garner international support? This article argues that the use of social media is a unique form of public diplomacy through which rebels project a favorable image to gain that support. It analyzes the Libyan civil war, during which rebels invested considerable resources in diplomatic efforts to gain US support. The study entails collecting original data, and finds that rebel public diplomacy via Twitter increases co-operation with the rebels when their message (1) clarifies the type of regime they intend to create and (2) emphasizes the atrocities perpetrated by the government. Providing rebels with an important tool of image projection, social media can affect dynamics in an ever more connected international arena.